"Bringing the library to you!". Issue 5 (11th May 2015) - Nicholas, Pauline; Sterling, Jerdaine; Davis, Rochelle; Lewis, Jessica C; Mckoy-Johnson, Faith; Nelson, Karlene; Tugwell, Yolanda; Tyrell, Karen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to assess the recent outreach service efforts of the University of the West Indies (UWI) Main Library in the form of a Hall of Residence Librarian Programme. The aim of the programme was to minimize library anxiety through partnership with the Office of Students Services. Design/methodology/approach – The transition from the secondary to the tertiary level is not always the smoothest for some students. On the islands of the English-speaking Caribbean, such as Jamaica, it can be especially difficult as some matriculants have never used an automated library. These students often experience great difficulty in effectively using the library which may result in them shying away from doing so and thus negatively impact the quality of their work. The UWI, the UWI Main Library, Mona campus, Jamaica has sought to address this challenge through the development of an outreach project to the first-year students entitled the Halls of Residence Librarian (HRL) programme. Findings – This new form of library outreach on The UWI Mona campus has yielded the offering of library services in new locations, strategic partnerships, increased interactions with the first-year students and a greater awareness of these students' needs. Most importantly, it was very effective in reducing library anxiety among the first-year students. Research limitations/implications – The "low" turnout to Research Rescue was largely attributed to the fact that this programme was entirely optional for the students, and it was not affiliated with any compulsory course or class. There was also the issue of a lack of incentives to boost student attendance at these sessions. Originality/value – This initiative is untested in the English-speaking Caribbean. The paper explores the outreach efforts of the library at the Mona campus of The UWI and seeks to add to the limited body of literature on Academic Library Outreach in the Caribbean.